Re-Orienting Class Analysis: Working Classes as Historical Formations - Camfield, David (Science & Society, 2004)
In order to conduct better class analysis, we need class theory that rises to the challenge of understanding class as a structured social process and relationship taking place in historical time and specific cultural contexts. The study of working classes as historical formations requires the replacement of underdeveloped concepts with theory adequate to the task. This theory should incorporate the knowledge that class never exists outside of other social relations such as gender and race, but is always mediated by those relations, and vice versa. Marx, Gramsci, Thompson and autonomist Marxism, enriched with the appreciation of the multidimensional nature of social being produced by feminism and other perspectives arising from struggles against oppression, provide important resources for the development of such a theory.